Dapoxetine for the management of premature ejaculation (Bangladesh Journal of Psychiatry, 2020)
Premature ejaculation is the most prevalent male sexual disorder and is more common in South Asia. Bangladesh is no exception. Premature ejaculation causes dissatisfaction in the relationship, frustration for the patient and partner as well as reason of marital failure. Since 1970s sex therapy was the mode of treatment for premature ejaculation. Now treatment with drugs also seems effective. Now a days dapoxetine is used in Bangladesh for the treatment of premature ejaculation. The aim of the study was to determine the efficacy and tolerability of dapoxetine in patients with premature ejaculation. It was a prospective study conducted in private chamber of Dhaka city during the period of March 2016 to February 2017. A total of 60 patients within 21 to 75 years were enrolled in the study according to criteria of International Society for Sexual Medicine (ISSM). We determined the efficacy of dapoxetine 30 mg/day for 12 weeks. The primary endpoint was intra vaginal ejaculatory latency time (IELT) measured by stopwatch. Safety and tolerability were assessed. All analysis was done on an intention-to-treat basis. The results showed that, dapoxetine significantly prolonged IELT (p